VD_FINDINFO HC / 2015 / 237 vom 4. März 2015 - VD Tribunal cantonal (2015)
DÉCISION D'IRRECEVABILITÉ, MOTIVATION DE LA DEMANDE, CONCLUSIONS | 319 let. b ch. 2 CPC (CH), 321 al. 1 CPC (CH), 326 CPC (CH), 50 al. 2 CPC (CH)